Pertumbuhan Anak Kambing Peranakan Etawah (PE) Sampai Umur 6 Bulan di Pedesaan - Sulaksana, Indra (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The research on the growth of Peranakan Etawah goat until six months-old during rainy and drought season  was  done  in  Petaling  Jaya  village Kecamatan  Kumpeh  Kabupaten  Muaro  Jambi.  Ninety  three Peranakan Etawah goats were used as sample based on the date of birth. Survey method was used to obtained satisfactory  data,  throughout  interview,  recording  and  weighting  of  body  goat.  Body  weight,  weaning weight, 6 months old-weight, pre weaning weight gain and 6 months old-weight gain were recorded during observation. Result showed that average of birth weight; weaning weight; 6 months old-weight; pre weaning weight  gain  and  body  weight  gain  obtained  were  2.33  ±  0.45  kg;  9.72  ±  194  kg;  13.24  ±  3.28  kg;  81.76  ± 20.69  and  46.07  ±  24.92  gr,  respectively.  In  conclusion,  the  growth  of  Peranakan  Etawah  goat  was  not affected (P>0.05) by season for weaning weight, 6 months old-weight and pre  weaning weight gain as well, but season had significantly effect (P<0.05) on  weight of birth and 6 months old weight gain.